Iron Oxide–Modified Carbon Electrode and Sulfate-Reducing Bacteria for Simultaneous Enhanced Electricity Generation and Tannery Wastewater Treatment - Miran, Faiz; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Akram, Sadia (Frontiers in Bioengineering and Biotechnology, 2021)
The microbial fuel cell (MFC) is emerging as a potential technology for extracting energy from wastes/wastewater while they are treated. The major hindrance in MFC commercialization is lower power generation due to the sluggish transfer of electrons from the biocatalyst (bacteria) to the anode surface and inefficient microbial consortia for treating real complex wastewater. To overcome these concerns, a traditional carbon felt (CF) electrode modification was carried out by iron oxide (Fe3O4) nanoparticles via facile dip-and-dry methods, and mixed sulfate-reducing bacteria (SRBs) were utilized as efficient microbial consortia. In the modified CF electrode with SRBs, a considerable improvement in the bioelectrochemical operation was observed, where the power density (309 ± 13 mW/m2) was 1.86 times higher than bare CF with SRBs (166 ± 11 mW/m2), suggesting better bioelectrochemical performance of an SRB-enriched Fe3O4@CF anode in the MFC. This superior activity can be assigned to the lower charge transfer resistance, higher conductance, and increased number of catalytic sites of the Fe3O4@CF electrode. The SRB-enriched Fe3O4@CF anode also assists in enhancing MFC performance in terms of COD removal (>75%), indicating efficient biodegradability of tannery wastewater and a higher electron transfer rate from SRBs to the conductive anode. These findings demonstrate that a combination of the favorable properties of nanocomposites such as Fe3O4@CF anodes and efficient microbes for treating complex wastes can encourage new directions for renewable energy–related applications.